Reconstruction of Distal Hind Limb Injuries in Cats Using the Caudal Superficial Epigastric Skin Flap - Bauer, M. S.; Salisbury, S. Kathleen (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
Four cats were admitted for treatment of traumatic wounds distal to the tarsus. The caudal superficial epigastric skin flap was used to reconstruct each wound. In two cats, an initial flap that included all four mammary glands was attempted, but the segment of the flap that incorporated the first mammary gland underwent necrosis. Caudal superficial epigastric flaps that included mammary glands ## 2, 3 and 4 survived completely in three cats. In one cat the distal 3.0 cm, including the second mammary gland, underwent necrosis after a seroma formed. These flaps covered defects that extended beyond the tarsus in all cats and to the digits in two cats.Four cats with traumatic wounds distal to the tarsus underwent reconstructive surgery. Caudal superficial epigastric flaps that included mammary glands ## 2, 3 and 4 were used to reconstruct the wounds. In two cats, all four mammary glands were initially included with the flap. In these two cats, the distal portions of the flaps including the first mammary gland underwent necrosis. The necrotic areas were debrided and the flaps were repositioned to cover the defects. The remainder of these flaps and one flap that included mammary glands ## 2–4 survived completely. All flaps covered defects that extended beyond the tarsus in all cats and to the digits in two cats.
Keywords: Caudal superficial epigastric; skin flap; wounds